Screening integration : recasting Maghrebi immigration in contemporary France - Durmelat, Sylvie; Swamy, Vinay (University of Nebraska Press, 2011)
North African immigrants, once confined to France's social and cultural margins, have become a strong presence in France's national life. Similarly, descendants of immigrants from Morocco, Algeria, and Tunisia have gained mainstream recognition as filmmakers and as the subject of films. The first collective volume on this topic, Screening Integration offers a sustained critical analysis of this cinema. In particular, contributors evaluate how Maghrebi films have come to participate in, promote, and, at the same time, critique France's integration. In the process, these essays reflect on the co.